Impacts of Education's Intervention on Solid Medical Waste Management in Improving Knowledge, Attitude, and Behavior of Medical Health Workers - Sofia Sofia; Wiku ST Yogasmara; Hafni Andayani; Ratna Idayati (Britain International of Exact Sciences (BIoEx) Journal, 2021)
The purpose of this study was to determine the effect of providing education on increasing knowledge, attitudes, and behavior of medical officers in solid medical waste management at the Regional General Hospital dr. Zainoel Abidin Banda Aceh, Indonesia. The research design used was a quasi experiment with the Wilcoxon comparison test. The research sample was the medical officer of dr. Zainoel Abidin Banda Aceh as many as 94 people who were divided into treatment and control groups. Knowledge, attitude, and the behavior of medical personnel was measured by interview using a questionnaire. The results showed that there was an effect of educational interventions on increasing the knowledge, attitudes, and behavior of medical personnel in the management of medical solid waste in the treatment and control groups (p <0.05). The results of the Wilcoxon test between the treatment groups on knowledge, attitudes, and behavior before and after the educational intervention showed a significant difference (p = 0.000), whereas in the control group between before and after the educational intervention did not show a difference with the p-value of knowledge (p = 0.102); attitude and behavior (p = 0.157). In the control group, the level of knowledge, attitudes and behavior tends to remain at a sufficient level. The conclusion of this study shows that educational interventions can provide an increase in the knowledge, attitudes and behavior of medical personnel in implementing solid medical waste management at dr. Zainoel Abidin Banda Aceh.